Probing compressibility of the nuclear interior in wild-type and lamin deficient cells using microscopic imaging and computational modeling - González Avalos, Paula; Reichenzeller, Michaela; Eils, Roland; Gladilin, Evgeny (Journal of biomechanics, 2011)
Mechanical properties of the cell nucleus play an important role in maintaining the integrity of the genome and controlling the cellular force balance. Irregularities in these properties have been related to disruption of a variety of force-dependent processes in the cell, such as migration, division, growth or differentiation. Characterizing mechanical properties of the cell nucleus in situ and relating these parameters to cellular phenotypes remain challenging tasks, as conventional micromanipulation techniques do not allow direct probing of intracellular structures. Here, we present a framework based on light microscopic imaging and automated mechanical modeling that enables characterization of the compressibility of the nuclear interior in situ. Based entirely on optical methods, our approach does not require application of destructive or contacting techniques and it enables measurements of a significantly larger number of cells. Compressibility, in this paper represented by Poisson's ratio ν, is determined by fitting a numerical model to experimentally observed time series of microscopic images of fluorescent cell nuclei in which bleached patterns are introduced. In a proof-of-principle study, this framework was applied to estimate ν in wild type cells and cells lacking important structural proteins of the nuclear envelope (LMNA−/−). Based on measurements of a large number of cells, our study revealed distinctive changes in compressibility of the nuclear interior between these two cell types. Our method allows an automated, contact-free estimation of mechanical properties of intracellular structures. Combined with knockdown and overexpression screens, it paves the way towards a high-throughput measurement of intracellular mechanical properties in functional phenotyping screens.
Gesehen am 24.03.2022